The Ability-Achievement Model Versus the Response to Intervention Model: Which Model is More Accurate in the Assessment of Diagnosing Students with Learning Disabilities? - Camp-McCoy, Debra (Journal of the American Academy of Special Education Professionals, 2012)
The Ability-Achievement Model is reviewed for efficacy in comparison to the Response to Intervention Model when diagnosing students with possible learning disabilities. The research will address the success of Ability-Achievement Model versus the Response to Intervention Model when successfully diagnosing students with learning disabilities was used to draw such conclusions as are listed throughout this paper. Studies on both models have shown inconsistencies in reference to correctly diagnosing students as having a learning disability. In the field of education, the inconsistencies in the data is troubling due to the sensitive nature that surrounds the incorrect diagnosis of a student as having an actual learning disability or not having said disability. Due to these findings, both models of identification are suitable only if used together over a specific period of time in the accurate diagnosis of establishing if a learning disability is present.